Balloon dilation of benign esophageal rings or strictures: a randomized clinical trial comparing two different inflation times. Issue 2 (1st March 2014) - Wallner, O.; Wallner, B.
Summary: Although balloon dilatation is the primary treatment for benign dysphagia, information about the optimal inflation time is lacking. The aim of the current pilot study was to compare 10 seconds inflation time with 2 minutes inflation time, regarding the efficacy. Twenty patients with symptomatic strictures were prospectively studied in a randomized fashion. The 10-second group required an average of 1.4 dilations per patient; the 2-minute group required an average of 1.5 dilations per patient. This pilot study indicates that 10 seconds inflation time is as effective as 2 minutes. Because the treatment is both painful and unpleasant, this is an important finding.